Port Concessions in Chile : Contract Design to Promote Competition and Investment - Foxley, Juan; Mardones, José Luis (World Bank, Washington, DC, 2012)
The objective of Chile's port reform, is to encourage investments for improved port equipment, in the hope that this will lead to more efficient service, in part by attracting larger, more modern ships. The first four major concessions, under which integrated terminals are run exclusively by private companies, started operations in January 2000. The integrated approach to port services replaces a system of free entry of multiple stevedoring companies. This note reviews how the concessions were designed: the criteria for the winning bids, the rules to prevent concessionaires' abusing their monopoly power, the rules to encourage investment, and the provisions for redundant workers.